2022
DOI: 10.13005/ojc/380426
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategy to Amido Alkyl Naphthols from Pyrazole Aldehydes using Silica Supported NaHSO4.SiO2 as an efficient Heterogeneous Catalyst

Abstract: A facile and eminent method has been reported for the preparation of amido alkyl naphthols. Amido alkyl naphthol derivatives were synthesized by the condensation of pyrazole aldehydes, β-naphthol and acetamide in the presence of a heterogeneous SiO2 supported sodium hydrogen sulphate catalyst using acetic acid as a solvent. This protocol is advantageous for its shorter reaction hours, simplest workup technique, excellent yields with easy recovery and reusability of the catalyst.1H, and 13C Nuclear Magnetic Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The application of other heterogeneous catalysts to the multicomponent Mannich reaction leading to the formation of amidoalkyl naphthols is summarized in Table 3, Refs. [93][94][95][96].…”
Section: Other Types Of Heterogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of other heterogeneous catalysts to the multicomponent Mannich reaction leading to the formation of amidoalkyl naphthols is summarized in Table 3, Refs. [93][94][95][96].…”
Section: Other Types Of Heterogeneous Catalystsmentioning
confidence: 99%
“…Perci et al reported the synthesis of a series of pyrazole-containing amidoalkyl naphthols by using silica-supported sodium hydrogen sulfate (NaHSO 4 .SiO 2 ). Although in some instances the targeted amidoalkyl naphthols were obtained in very high yields, this method requires longer reaction times and the use of acetic acid as a solvent [95]. Dipake et al prepared a zeolite catalyst, zirconium silicate, and utilized it for the preparation of amidoalkyl naphthols.…”
Section: Other Types Of Heterogeneous Catalystsmentioning
confidence: 99%